PERBEDAAN TINGKAT KECEMASAN IBU BERSALIN DI PUSKESMAS DENGAN DI BIDAN PRAKTIK MANDIRI - Fatihatul Hayati (Jurnal Akademika Baiturrahim Jambi, 2018)
Maternal mortality rate is higher in assisted childbirth rather than that of natural childbirth. The unresolved anxiety can cause childbirth to last longer and lead to assisted childbirth. Childbirth environment at the hospital can increase maternal anxiety which results in disturbing uterine contraction so that action should be taken to speed up the delivery process. The aim of this study was to determine the difference in anxiety level between mothers who give birth at the Public Health Center and those who give birth at Private Midwife Center. The study was conducted by cross-sectional design on 74 mothers in labor. They were divided into two groups: those who give birth at Public Health Center and those who give birth at Private Midwife Center with consecutive sampling technique.Data were then analyzed by conducting Independent T test. The result showed that the first group had higher average score of anxiety than the second group with p value < 0.05.The study suggested that there was significant difference between giving birth at Public Health Center and giving birth of Private Midwife Center